LAJU PERTUMBUHAN DAN EFISIENSI PAKAN IKAN NILA (Oreochromis niloticus) YANG DIPELIHARA DALAM KOLAM TERPAL YANG DIPUASAKAN SECARA PERIODIK - Intan Permata Sari; Yulisman .; Muslim . (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACT    Starved was one effort that can reduce the feed consumption and feed residues without decreasing growth of cultured fish. The purpose of this research was to determine the effect of starved periodically to the specific growth rate and feed efficiency of tilapia reared in the pond. The research had been conducted in Laboratorium Budidaya Perairan, Faculty of Agriculture, Sriwijaya Unversity on April – Juni 2016. This research method used Completely Randomized Design with four treatments and three replications that was every day feed without starvation (P0), one day feed one day starvation (P1), two days feed one day starvation (P2) and three days feed one day starvation (P3). Parameters of this research are specific growth rate, feed efficiency, survival rate and water quality (temperature, pH, DO, ammonia). The result showed that starved periodically significantly effect to the growth rate and feed efficiency of cultured tilapia in the pond. Treatment P1 (one day feed one day starvation) gave highest specific weight growth rate and specific length growth rate which were 2.32%.day-1 and 1.27%.day-1 then feed efficiency was 84.46%. The highest survival rate occurred in treatment P1 (one day feed one day starvation) 82%. Water quality of this research were temperature 27.0-31.5 oC,  pH 6.8-7.9, dissolved  oxygen 4.53-7.23 mg.L-1, and ammonia 0.01-0.30 mg.L-1. Keywords : Feed Efficiency, Specific growth rate, Starved, , Tilapia.